(untitled) (Asia Pacific Journal of Social and Behavioral Sciences, 2012)
This study determined the Philippine government’s investment in initial education both in elementary and secondary levels from 2007-2010 and their outcomes in these years such as: the enrolment, cohort survival, dropout, completion and achievement. These basic education indicators were analyzed in order to determine whether the government’s spending translated to quality educational outcomes. It is expected that when government spending increased cohort survival rates, completion rates and achievement rate would increase and there should be a decrease in dropout rate. The Department of Education in 2010 has targeted that elementary education 79% cohort survival rate, 77% completion rate and 4.0 dropout rate; in secondary education to have 81% cohort survival rate, 76% completion rate and 5.0 dropout rate. It is also expected that in both levels, a 75% above achievement rate be realized. Government spending increased during the span of four years as well as the enrolment and the other outputs of education. However, the increasing trends did not meet the expected desired outcomes. The study further found that there are inequities in the distribution of budget per capita by region. These findings suggest that the government had to redirect policies in budget allocation for initial education based on priority areas by region considering performance and poverty incidence. A more efficient spending and financing be institutionalized.